University entrepreneurial intentions: mainland and insular regions – are they different? - Lopes, João (2020)
Purpose – The purpose of this paper is to involve the differences in the entrepreneurial intentions of student at higher education institutions (HEIs) in the Portuguese regions (mainland and insular). Design/methodology/approach – Applying a sample of 594 valid responses, the authors analyzed the data according to linear regression models. Findings – The results convey how HEI students generally do not intend to become entrepreneurs in both the mainland and the insular regions. Although HEI students broadly do not aim to launch their own businesses, the results show that students in mainland regions feel they have the skills to start a business and drive it to success. In insular regions, students feel encouraged by their friends and family to set up their own business. When comparing insular and mainland regions, the results demonstrate how in insular regions, there is a greater probability that HEI students become entrepreneurs than in the mainland regions. Furthermore, entrepreneurial intentions in the mainland regions develop in terms of “opportunities” while driven by necessity in the insular regions. Practical implications – This furthermore makes recommendations to regional governments and to HEIs in order to enable better encouragement of entrepreneurship in academia. Originality/value – This study is original and innovative due to its comparison of the entrepreneurial intentions prevailing in mainland and insular regions and may propose new highlights to the academic scientific literature.